Impacts of Social Protection Programmes in Ethiopia on Child Work and Education. - Yablonski, J; Woldehanna, T (Young Lives (Project), DFID (University of Oxford), 2008)
Social protection measures are becoming an increasingly important policy tool for African governments. These measures have important potential for reducing poverty and positive impacts on child well-being. However, Young Lives research has found that different social protection programmes in Ethiopia have had unexpected impacts on girls’ and boys’ participation in school, and in paid and unpaid work. In order to create a win-win situation where both national economic development and children’s rights are realised, it is crucial to have a deeper understanding of the relationship between social protection programmes and children’s time use.